A resampling algorithm to detect continuous gravitational-wave signals from neutron stars in binary systems. (27th September 2019) - Singhal, A; Leaci, P; Astone, P; D'Antonio, S; Frasca, S; Intini, G; La Rosa, I; Mastrogiovanni, S; Miller, A; Muciaccia, F; Palomba, C; Piccinni, O
Abstract: A rapidly rotating neutron star (NS) with non-axisymmetric deformations is an interesting type of continuous gravitational-Wave (CW) source for the advanced LIGO–Virgo detectors. Within the sensitivity bands of these detectors, more than half of the known pulsars (i.e. 1200) in our galaxy are in binary systems. All CW signals are modulated by the doppler effect due to Earth's motion, while for sources in binary systems there is an extra modulation due to the source orbital motion, which further decreases the detectability of the signal, if not properly taken into account. In order to correct for these modulations, one would need to know at least the orbital parameters and source sky location with very high accuracy. For unknown parameters the correction implies an extensive computational burden. In this paper we investigate—for the first time—the application and robustness of binary time-domain corrections to directed narrowband searches through the stroboscopic resampling, which has already been applied in several CW searches for isolated NSs. We also present a 90% confidence-level sensitivity estimation for a Scorpius X-1 directed narrowband search on publicly available data from the second observing advanced LIGO–Virgo run.